Screening and profiling of mercury-resistant Azotobacter isolated from gold mine tailing in Pongkor, West Java - Suryatmana, Pujawati; Handayani, Sri; Bang, Sunbaek; Hindersah, Reginawanti (Brawijaya University, 2024)
Mercury (Hg) is a hazardous pollutant produced during the amalgamation of gold extraction. The environmental problems related to improper Hg waste management have become progressively concerning. Hg contamination in environments can be removed by using bioremediation technology. Utilizing Hg-resistant (HgR) microorganisms in Hg bioremediation is a crucial strategy. Azotobacter is one of the potential microbes for Hg bioremediation bioagent due to exopolysaccharides synthesis that binds the heavy metal. The study's main objective was to select and profile a novel Hg-resistant Azotobacter isolated from heavily Hg-contaminated soil and tailing of artisanal and small-scale gold in Pongkor area, West Java, Indonesia. The completely randomized design was used for profiling Azotobacter-HgR and included Hg values of 0, 1, 10, 100, 200, and 400 mg/L. Further, Azotobacter isolate bioassay steps included soil contaminated with Hg, soil contaminated with Hg + Azotobacter sp. S6.a, soil contaminated with Hg + consortium. The profiling results revealed that four Hg-resistant isolates were Azotobacter sp. S5, Azotobacter sp. S6, Azotobacter sp. S6.a, and Azotobacter sp. S9. More importantly, Azotobacter sp. S5 followed by Azotobacter sp. S6.a was found to be the most resistant to Hg exposure at a concentration of 400 mg/L. The Azotobacter sp. S9. produced the lowest EPS, but had the highest activity of nitrogenase and organic acid production. Meanwhile, Azotobacter sp. S6.a. produced the highest EPS. Isolate S5 showed the highest potential as a resistant PGPR-Hg isolate for enhancing the growth of sorghum in Hg-contaminated soil. Sorghum plants accumulate Hg from the soil in the roots but not in the shoots. Present findings suggest that these two isolates have the potential to be used as biological agents to rehabilitate Hg-contaminated soil in Pongkor area.